Cilostazol may improve cognition better than clopidogrel in non-surgical adult patients with ischemic moyamoya disease: subanalysis of a prospective cohort. (4th May 2019) - Ando, Satoshi; Tsutsui, Shouta; Miyoshi, Kenya; Sato, Shinpei; Yanagihara, Wataru; Setta, Kengo; Chiba, Takayuki; Fujiwara, Shunrou; Kobayashi, Masakazu; Yoshida, Kenji; Kubo, Yoshitaka; Ogasawara, Kuniaki
ABSTRACT: Objective : Adult patients with ischemic moyamoya disease (MMD) who receive treatment with antiplatelet drugs reportedly show improvements in neuropsychological test scores after around 2 years. The purpose of the present study subanalyzing the same patient cohort used in a previous study was to determine which antiplatelet drug, clopidogrel or cilostazol, results in better improvement of cognitive function among non-surgical adult patients showing ischemic MMD without severe hemodynamic compromise. Methods : Sixty-six patients without cerebral misery perfusion on 15 O gas positron emission tomography were treated with pharmacotherapy alone. Patients ≥50 years old and <50 years old initially received clopidogrel and cilostazol, respectively. Any patient suffering side effects of the antiplatelet drug switched to the other antiplatelet drug. Neuropsychological tests were performed at study entry and at the end of the 2-year follow-up, and differences in each neuropsychological test score between the two time points (second test score – first test score) were calculated and defined as Δ scores. Results : Among the five neuropsychological tests, Δ scores for two tests were significantly greater in patients treated with cilostazol (n = 36) than in those treated with clopidogrel (n = 30), and Δ scores of the remaining three tests did not differ between patient groups. Based on Δ scores, 15 patients (23%) were defined as showing interval cognitive improvement. On multivariate analysis, cilostazol administration (95% confidence interval, 1.19–193.98; P = 0.0361) represented an independent predictor of interval cognitive improvement. Conclusions : Cilostazol may improve cognition better than clopidogrel in non-surgical adult patients with ischemic MMD.